Alcuni aspetti performativi del travestimento animale: l'esempio di Dolone il lupo (Mantichora. Italian Journal of Performance Studies, 2020)
This paper will focus on “wolf” performance of the homeric Dolon, through an examination of the epic poem. It will attempt to highlight two arguments. First it will outline the elements of mirroring between the human sphere and the animal, by relating Dolon with other protagonists of the storyline; than it will show how the wolf skin interferes with the Dolon’s identity, not by itself but together with the context in the whole and with other elements, with particular reference to the vocal sphere.